Frontispiece: Efficient Degradation of Phenol and 4‐Nitrophenol by Surface Oxygen Vacancies and Plasmonic Silver Co‐Modified Bi2MoO6 Photocatalysts. Issue 69 (10th December 2018) - Shen, Huidong; Xue, Wenwen; Fu, Feng; Sun, Jiefang; Zhen, Yanzhong; Wang, Danjun; Shao, Bing; Tang, Junwang
Abstract : Using a reliable solvothermal process combined with an impregnation–calcination approach, an oxygen‐vacancy‐rich Ag/Bi2 MoO6 photocatalyst was fabricated that was active for both phenol and 4‐nitrophenol degradation. This work provides an effective strategy for the design and fabrication of highly efficient photocatalysts through integrating surface oxygen vacancies and surface plasmon resonance effect of nanoparticles and the potential to water treatment and air purification. For more information, see the Full Paper by F. Fu, D. J. Wang, B. Shao, J. W. Tang et al. onpage 18463 ff.